Optimalisasi Digital Public Relations Dalam Meningkatkan Citra Pasar Digital UMKM: Studi Deskriptif Kualitatif di Divisi Social Media dan Digital Marketing PaDi UMKM Jakarta - Shifa Nurfitri Aulia Isti; Tria Patrianti (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
PaDi UMKM is a limited liability company (PT) and is classified as a closed PT. PT PaDi UMKM was established in 2020. The purpose of this study is to determine the optimization of digital public relations in improving image. The theories used in this study are digital public relations theory and image theory. This research approach uses a descriptive qualitative method, with primary data collection techniques in the form of interviews with three informants and an expert, and secondary data in the form of documentation, both data and images. The results of the study indicate that the optimization of digital public relations by PaDi UMKM plays an important role in improving brand image. Referring to Clea Bourne's theory, PaDi UMKM utilizes digital tools such as blogs, articles, and social media for one-way and two-way communication. This strategy is supported by media monitoring that includes content planning, trend utilization, and sentiment analysis to understand public opinion. The success of building a positive image is supported by attractive visual content, inspirational storytelling, and active interaction with the audience, as well as collaboration with the Ministry of State-Owned Enterprises that strengthens credibility. Challenges in the form of user complaints about the application system are handled through fast responses and responsive customer service. With a solution-oriented approach, appropriate education, and the use of digital platforms, optimizing digital public relations not only increases positive public perception but also strengthens customer loyalty, making PaDi UMKM a reliable B2B marketplace.